WELFARE ANALYSIS OF RICE FARMING BUSINESS AT KOTAR VILLAGE, HAMPARAN PERAK DISTRICT, DELI SERDANG REGENCY - Tarigan, Muhammad Handoko; Fadlan, Ahmad; Ramadhan, Anggia; Siswanto, Annisa Anggraini; Khadafi, Rachmad (Proceeding International Conference Keputeraan Prof. H. Kadirun Yahya; Vol 1 No 1 (2022): 1st International Conference Keputeraan Prof. Kadirun Yahya, 2022)
Welfare Analysis of Rice Farming in Kota Datar Village, Hamparan Perak District, Deli Serdang Regency. The problems in this research are broad land, production, price, education, power work, capital, policy government and technology are factors that affect the welfare of farmers. This study aims to analyze the factors that influence the welfare of farming in Kota Datar Village, Hamparan Perak District, Deli Serdang Regency. The data were processed using factor test analysis and then using multiple linear regression. The data obtained from distributing the questionnaires were processed using SPSS software Version 23.0 For Windows . The results showed that of the 8 variables analyzed with the analytical model factor consists from 3 factor that is factor price, factor production and factor land area. Based on multiple linear regression analysis, it shows that price, production and land area have a significant and significant effect on the welfare of farming in Kota Datar Village, Hamparan Perak District, Deli Regency Serdang.